(untitled) (Journal of Philosophy Culture and Political Science, 2022)
Abstract: Philosophers have been discussing the relationship between man, God and nature for thousands of years. Muslim or not, the questions are the same: do we humans have an unchanging or changing basic nature? If so, what does it look like? What is God’s connection with human nature? And how do the answers to these questions affect how we think about politics, economics, psychology, sociology, theology, philosophy, and even science? In this scientific article, the authors tried to answer these questions and give examples from the point of view of Islamic philosophers, considering the holy scriptures (the Quran and the Sunnah) as a fundamental set of premises. They classify and formulate different views on human nature into three categories, each of which has its own historical origin. These categories are - the ratio of the world and nature, the ratio of nature and man, the ratio of nature and God. In the context of such reflections, the main philosophical and religious ideas and representatives of Kazakh philosophy are also considered. The conclusion of the study speaks about the significance of these philosophical concepts for modern philosophy. Keywords: philosophy, islam, man, God, nature.